PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN COOPERATIF TIPE STAD - Hawani Akmal (JURNAL PENA EDUKASI, 2019)
Abstract: Before the action was done the category average teacher teaching outcomes were in the low category with a completeness level of 44.84% (21 people completed from 48 teachers). In the second cycle after the action was taken the teacher's teaching results were in the moderate category with a completeness rate of 79.20% (38 people completed from 48 teachers). In the second cycle after further action was taken as a result of the reflection of the first cycle the teacher's learning outcomes were in the good (high) category with a completeness level of 97.92%, in this cycle only 1 teacher was incomplete. The activeness of the teacher in participating in Mathematics learning in school after taking good action in the first cycle and second cycle increases. This is indicated by the frequency of teacher attendance at the lessons is getting better. Doing and gathering assignments on time, there is an increase in teachers who appear in solving questions, and more and more teachers are answering questions raised by the teacher. Keywords: Teaching Results, STAD Abstrak: Sebelum dilakukan tindakan kategori rata-rata hasil mengajar guru berada pada kategori rendah dengan tingkat ketuntasan 44,84 % (21 orang yang tuntas dari 48 guru). Pada siklus II setelah dilakukan tindakan hasil mengajar guru berada pada kategori sedang dengan tingkat ketuntasan 79,20 % (38 orang yang tuntas dari 48 guru). Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil refleksi siklus I hasil belajar guru berada pada kategori baik (tinggi) dengan tingkat ketuntasan 97,92 %, pada siklus ini hanya 1 orang saja guru yang tidak tuntas. Keaktifan guru dalam mengikuti pembelajaran Matematika di sekolah setelah dilakukan tindakan baik pada siklus I dan siklus II semakin meningkat. Hal ini ditandai dengan frekuensi kehadiran guru mengikuti pelajaran semakin baik. Mengerjakan dan mengumpulkan tugas-tugas tepat waktu, terjadi peningkatan guru yang tampil dalam penyelesaian soal soal, dan semakin banyak guru yang menjawab pertanyaan yang dilontarkan guru. Kata kunci: Hasil Mengajar, STAD